(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
New taxonomic and biostratigraphic investigations on the late Carnian to Rhaetian (Upper Triassic) platform conodonts from the Pizzo Mondello section (Western Sicily, Italy, Sicano basin) are here presented. Pizzo Mondello is one of the two GSSP candidates for the Carnian/Norian boundary; the section is a 430 m thick continuous succession of upper Carnian to upper Norian marine limestones (Scillato Formation), characterized by uniform facies and high sedimentation rates, and ca. 20 m of Rhaetian white calcilutites (Portella Gebbia limestone). Pizzo Mondello offers one of the most complete conodont records for this time interval in the Tethys. The conodont faunas are characterized by a large variety of species, belonging to the genera Carnepigondolella, Epigondolella, Metapolygnathus, Misikella, Mockina, Neocavitella, Norigondolella, Paragondolella, and Parvigondolella. The richness of the populations allowed a detailed revision and description of all the Upper Triassic species and morphotypes recovered. The revision of the problematic species Carnepigondolella nodosa and "Metapolygnathus communisti B" was thus possible, leading to the establishment of two new species: Carnepigondolella tuvalica n.sp. and Carnepigondolella gulloae n.sp. The latter species would be a good proxy for the Carnian/Norian boundary in the case that the FAD of Halobia austriaca (sample FNP135a) will be selected as the primary biomarker for the base of the Norian.